2009
DOI: 10.1093/toxsci/kfp281
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Specific Ablation of Integrin-Linked Kinase in Mice Results in Enhanced and Prolonged Cell Proliferation and Hepatomegaly after Phenobarbital Administration

Abstract: We have recently demonstrated that disruption of extracellular matrix (ECM)/integrin signaling via elimination of integrin-linked kinase (ILK) in hepatocytes interferes with signals leading to termination of liver regeneration. This study investigates the role of ILK in liver enlargement induced by phenobarbital (PB). Wild-type (WT) and ILK:liver-/- mice were given PB (0.1% in drinking water) for 10 days. Livers were harvested on 2, 5, and 10 days during PB administration. In the hepatocyte-specific ILK/liver-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Previous studies show that ILK mediated ECM signaling inhibits hepatocyte proliferation and ILK deletion results in enhanced proliferation after PHX or treatment with nuclear receptor agonists (1,9,11). Changes in ECM occur after toxin-induced liver injury and ILK signaling has been reported to play a role in process of injury development, and subsequent recovery and survival response (12,13,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies show that ILK mediated ECM signaling inhibits hepatocyte proliferation and ILK deletion results in enhanced proliferation after PHX or treatment with nuclear receptor agonists (1,9,11). Changes in ECM occur after toxin-induced liver injury and ILK signaling has been reported to play a role in process of injury development, and subsequent recovery and survival response (12,13,28).…”
Section: Discussionmentioning
confidence: 99%
“…ILK-mediated ECM signaling is known to exert inhibitory effects on hepatocyte proliferation and is one of the major ‘termination signals’ for liver regeneration. ILK-KO mice, which lack this inhibitory signal and thus have proliferative advantage due to termination defect, exhibit increased liver regeneration after partial hepatectomy as well as after administration of nuclear receptor agonists (1,9,11). Both these models do not involve massive liver injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the E t of path 3 was higher than the control, too. Integrins combined with ILK, and then regulated expression of cyclin D1 by activation of the ERK→MSK1/2→CREB pathway (path 3) [7]. Transfer of ILKoverexpressing hepatocytes resulted in continued high levels of expression of cyclin D1 and cyclin A proteins, indicating that, when overexpressed, ILK induces signaling pathways resulting in the stimulation of G1/S cyclin-Cdk activities, finally leading to hepatocytes entering S phase [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that hepatocyte differentiation and proliferation are greatly affected by extracellular matrix (ECM) through the integrin signaling pathway [6]. Recent research demonstrated that disruption of ECM/integrin signaling via elimination of integrin-linked kinase (ILK) in hepatocytes interferes with signals, leading to termination of liver regeneration [7]. However, the ECM/integrin signaling pathway is a complex signaling transduction network which is made up of many branches.…”
Section: Introductionmentioning
confidence: 99%